The Reusability and Coupling Metrics for Service Oriented Softwares - Huỳnh, Quyết Thắng (ĐHCN, 2016)
Service-oriented architecture (SOA) has inherited and developed based on some others such as object-oriented and component-based architecture. SOA is a method of developing software which represents reliability, efficiency and maintainability. However, to evaluate these advantages adequately, we need to have metrics to measure quality attributes. Until now, although many scientists have proposed a huge of metrics for object-oriented and component-based software, the evaluation of service-oriented software’s quality attributes has not been aware widely. Reuse and couple abilities are the most important attributes of service-oriented software. We assessed and chosen the most suitable metrics with service-oriented software based on comparison between many software architectures. Then, we modified these metrics to apply in SOA. In this paper, we propose two suites of metrics for reuse and couple and a suite of dynamic metrics. Developers with metrics can predict the cost of software development and maintenance. We use Web Service software for testing and evaluating. The results we gained were compared with other metrics applied in service-oriented software. These results applied in Web Service are also right for every SOA